Bovine nebovirus infection (review) - V. A. Mischenko; A. V. Mischenko; T. B. Nikeshina; Yu. V. Brovko; A. I. Kushlubaeva (Ветеринария сегодня)
Animal husbandry is one of the main agricultural industries in most countries over the world as well as in the Russian Federation, and its proﬁtability is determined by three main factors: the animal genetic potential, complete diet and freedom from infectious, invasive and mass non-infectious diseases. One of the most signiﬁcant and diﬃcult tasks is to generate and rear healthy young cattle. Digestive disorders clinically manifested by diarrhea resulting in apparent dehydration, toxemia, enophthalmos, membrane pathology, immunodeﬁciency and metabolic disorders are prevalent among neonatal calf diseases in early postnatal period. Massive diarrhea in neonatal calves is characterized by signiﬁcant polymorphism, involving a wide range of various factors including genetic, physiological, sanitary and hygienic as well as infectious factors. Infectious agents are the main causes of massive gastroenteritis in neonatal calves. In most cases viruses serve as triggers for gastrointestinal pathology development and bacteria play the secondary role. For a long time, rotaviruses, coronaviruses and pestiviruses have been believed to play the main role in etiology of massive neonatal calf diarrhea. In recent years, a number of new and understudied viruses, including kobuvirus, nebovirus, norovirus, torovirus and astrovirus, have been detected in fecal samples from diarrheic calves and their role in diarrhea development has not been deﬁnitively determined. Their role as primary pathogens, coinfection agents or commensals remains unclear. Recently these animal pathogens have widely spread in diﬀerent countries of the world. At the end of the XX century – beginning of the XXI century, large numbers of cattle were imported to the Russian Federation, including cattle from the nebovirus-infected countries. Data on nebovirus infection (occurrence, pathogen characteristics, disease clinical signs and epizootological features) are given in the paper.